Social Isolation and Aging in Zambia: Examining the Possible Predictors - Christopher Chabila Mapoma; Gift Masaiti (Journal of Aging Research)
This research paper examined social isolation and aging in Zambia by examining possible predictors. The paper produces evidence on risk factors likely to engender social isolation among the elderly population of Zambia. Snowball sampling was undertaken to select 690 adults aged 60 and over in communities as well as those living in homes for the aged. A structured questionnaire was used to solicit information from respondents. Results show that old people in Zambia experience forms of social isolation which exhibit themselves (but not limited to) through such factors as loss of appetite, stress, moody, hopeless, useless, unhappy, and lonely. On balance, however, the direction of association and the number of statistically significant findings suggest that associations between variables examined and risk factors associated with social isolation amongst older people in this analysis could explain the overall situation occuring currently in Zambia and probably other developing countries. In view of this, this study recommends that further work is needed to identify and explain details of factors of social isolation using techniques such as focus group discussions as well as in-depth interviews with key informants. Such approaches may even help to explain why, for example, sex seems not to be significant in determining indicators of social isolation.